Research progress in the establishment of mouse models of chronic rhinosinusitis - CHEN Yuan, SHEN Yang, WANG Ji, LU Tao, ZHENG Bowen, YANG Yucheng (Xin yixue)
Chronic nasal inflammation， such as rhinitis and sinusitis， is a common chronic disease that affects people’s quality of life for a long period of time. Its pathogenesis and mechanism are still unclear. The establishment of animal models is an effective approach to explore the pathogenesis， among which the establishment of mouse models of chronic nasal inflammation has been rapidly developed in recent years. The aim of this review is to summarize the research status of chronic rhinosinusitis and allergic rhinitis modeling in mice at home and abroad， especially the progress in eosinophilic chronic rhinosinusitis mouse models， which plays an important role in the development of new drugs to prevent and control chronic nasal inflammation or further elucidation of its pathogenesis.